Sulfur Biogeochemistry - Past and Present 2004
DOI: 10.1130/0-8137-2379-5.49
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemistry of metal sulfide oxidation in mining environments, sediments, and soils

Abstract: Metal sulfi de oxidation is the only major sulfate-generating biogeochemical process on Earth. It is a process of major environmental impact, causing acid rock drainage (ARD) or acid mine drainage (AMD), the development of acid sulfate soils, and aquifer contamination. Metal sulfi des are formed and oxidized in sediments. Metal sulfi de oxidation is also important for processing ores for metal recovery (e.g., in bioleaching applications).Chemical and biological processes interact in metal sulfi de oxidation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
76
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 81 publications
1
76
0
1
Order By: Relevance
“…Closing the cycle, the reduced iron generated during mineral attacks is re-oxidized by the microorganisms. Two ways of oxidation of the mineral sulfide have been proposed and depend upon its composition [11][12][13][14]. The so-called thiosulfate pathway oxidizes species like pyrite, molybdenite, and tungstenite, while sphalerite, chalcopyrite, arsenopyrite, and galena are oxidized via polysulfide pathway.…”
Section: Bioleaching Processmentioning
confidence: 99%
“…Closing the cycle, the reduced iron generated during mineral attacks is re-oxidized by the microorganisms. Two ways of oxidation of the mineral sulfide have been proposed and depend upon its composition [11][12][13][14]. The so-called thiosulfate pathway oxidizes species like pyrite, molybdenite, and tungstenite, while sphalerite, chalcopyrite, arsenopyrite, and galena are oxidized via polysulfide pathway.…”
Section: Bioleaching Processmentioning
confidence: 99%
“…When Fe(III) (hydr)oxides are dissolved, adsorbed or precipitated metals are released. Sulfate-reducing Bacteria or Archaea may also precipitate metals as metal sulfides (22,49,50).Primarily cultivation techniques have been used to enumerate prokaryotes involved in oxidation and reduction processes in sulfidic mine waste dumps (3,17,52,57,64). Cultivation techniques yield cell numbers merely according to physiological properties; therefore, only a subset of the whole microbial community is detected.…”
mentioning
confidence: 99%
“…It has been reported that the overall rate of polythionate oxidation is markedly slower than the rate of oxidation of thiosulphate (forming polythionate) in acidic, ferric-rich solutions (Druschel, Hamers, and Banfield, 2003). In contrast, polythionate degrades at low pH in the presence of sulphide (FeS 2 ) (Schippers, 2004).…”
mentioning
confidence: 99%
“…Tetrathionate formation has been reported as a product of pyrite oxidation at pH 2.9-8.6 in the presence of molecular oxygen, at pH 8 in the presence of MnO 2 , and at pH 2 in the presence of Fe(III) (Schippers, 2004). Other sources state that in order to minimize formation of polythionates during leaching, it is necessary to maintain the acid concentration at greater than 5 g/L H 2 SO 4 (Nugent, 1956;Druschel and Borda, 2006).…”
mentioning
confidence: 99%